Analisa Kadar Kromium VI [Cr (VI)] Air di Kecamatan Tanggulangin, Sidoarjo - Ary Andini (Faculty of Health Sciences Universitas Maarif Hasyim Latif, 2017)
Tanggulangin is one of the sub-districts in Sidoarjo district affected by Lapindo mudflow caused by oil drilling system error located in the area of Siring, Porong. Therefore it had impacted the water quality in around Lapindo mudflow area. The aim of this research was to analysis the levels of water Cr (VI) Tanggulangin district. Water sample was analyzed by spectrophotometer with wavelength of 540 nm and done using two (2) steps ,which were(1) establishment of standard curve and (2) determination of Cr (VI) in water. Ten (10) water samples were taken from various villages in the subdistrict Tanggulangin. Based on the results on level of water chromium VI [Cr (VI)] analyze showed 4 of 10 samples had levels of water Cr (VI)higher than standard 0,05 mg/L (PP No.82 tahun 2001), those sample were 1, 3,4 and 10.